Association of GALC, ZNF184, IL1R2 and ELOVL7 With Parkinson’s Disease in Southern Chinese - Li, Gen; Cui, Shishuang; Du, Juanjuan; Liu, Jin; Zhang, Pingchen; Fu, Yang; He, Yixi; Zhou, Haiyan; Ma, Jianfang; Chen, Shengdi (Frontiers in Aging Neuroscience, 2018)
Study Objectives: The aim of the study was to investigate the relationship between 22 single nucleotide polymorphisms (SNPs) and Parkinson’s disease (PD) in Chinese population. Methods: A total of 250 PD patients and 240 healthy controls were recruited. SNaPshot technique and polymer chain reaction were used to detect 22 SNPs. Results: rs8005172 of GALC, rs9468199 of ZNF184 and rs34043159 of IL1R2 were associated with in PD (rs8005172: p = 0.009, OR = 0.69, allele model, p = 0.010, additive model, p = 0.015, OR = 2.17, dominant model; p = 0.020, OR = 2.11, dominant model after adjustion; p = 0.036, OR = 1.47, recessive model after adjustion; rs9468199: p = 0.008, OR = 1.52, allele model, p = 0.008, additive model, p = 0.007, OR = 0.22, recessive model, p = 0.005, OR = 0.20, recessive model after adjustion; rs34043159: p = 0.034, OR = 1.31, allele model, p = 0.036, additive model). Conclusion: Our study revealed that GALC, ZNF184, IL1R2 were associated with PD in southern Chinese population. GALC was also associated with LOPD. ELOVL7 and ZNF184 were associated with EOPD. Besides, the trends of association of SATB1, NMD3 and FGF20 with PD were also found.